PTH-045 Integrated Alcohol And Hepatology Mdt: Reducing Alcohol-related Hospital Admission And Attendance. (9th June 2014) - Mannix, K; Patterson, K; Richardson, L; puravady, S; Owens, L; Richardson, P
Abstract : Introduction: In 2010 a joint position paper on behalf of British Society of Gastroenterology, the Alcohol Health Alliance UK, and the British Association for Study of the Liver highlighted that the most deprived lifestyle groups have up-to 15 times greater alcohol‐specific mortality and up to 10 times greater alcohol‐specific admissions to hospital. It therefore recommended that each acute hospital should develop a multidisciplinary approach to the care and management of people attending or admitted to hospital with an alcohol-related cause .1 Methods: We conducted a notes review of all patients attending or admitted to the hospital on more than 6 occasions in the previous 6 months. We also complied 3 in-depth case studies of our most frequent attenders. We investigated the reason for admission including medical and social confounders. We then looked at the range and number of medical and social disciplines involved in their care, discharge planning and aftercare. We spoke to our patients about why they had chosen to attend hospital and what they felt could be provided as an alternative. We developed an electronic early warning system to inform the Alcohol Team when a patient was admitted. This triggered referral to our integrated alcohol and hepatology consultant led MDT Results: Our investigations showed that the majority of patients had a range of support including key workers from a variety of voluntary agencies, housing agencies, GP's, primary care alcohol specialist nurses, social workers, homeless outreach, and specialist medical consultants from psychiatry to hepatology. However, much of this work was happening in isolation and was at times conflicting with no one organisation or professionals supporting or mapping out the patients journey. Importantl, y, the patients were unclear where to go for what, and were often utilising the ED as a failsafe when they were unsure or troubled. The MDT is a vehicle to ensure that the patient gets the right treatment at the right time by the right person; which has helped our patients better understand their care pathways and their aims. This has resulted in a significant reduction in hospital attendance and admission for this small but significant patient group. Conclusion: An MDT for alcohol-related admissions augments and centralises the expertise of health and social care partners in the development of truly patient centred shared plans of care. This leads to hospital admission only when appropriate and necessary Reference: 1 Moriarty K. A Joint Position Paper on behalf of the British Society of Gastroenterology, Alcohol Health Alliance UK, British Association for Study of the Liver – ALCOHOL-RELATED DISEASE Meeting the challenge of improved quality of care and better use of resources. 2010 Disclosure of Interest: None Declared.